Donating equipment to Zimbabwe. Issue 2 (3rd April 2018) - Thompson, Alice; Watson, Graham
Abstract : Donating medical equipment to poorer countries is not as simple as it might seem. In this article the authors describe a donation and teaching programme undertaken by the charity Medi Tech Trust in Zimbabwe. They also discuss some of the challenges that donating equipment, both new and used, entails.